it is related to simplification of algebraic terms

In terms of simplifying it to solve it more easily, you can use the properties of FOIL.

(a+b)*(c+d) = a*c+b*c+a*d+b*d

what you have is 2704 * 2209

To make it similar to the properties of FOIL, you can split the numbers up.

2704 = 3000 - 296

2209 = 2000 + 209

2704 * 2209 = (3000 - 296)*(2000 + 209) = 3000 * 2000 - 296 * 2000 + 209 * 3000 - 296 * 209

You can further simplify this by repeating the steps

-296*2000 = (-300 + 4) * 2000 = -300 * 2000 + 4 * 2000

209*3000 = (200 + 9) * 3000 = 200 * 3000 + 9 * 3000

-296 * 209 = (-300 +4)*(200 + 9)

I'm sure you can finish from here. It's essentially taking one method and repeating it multiple times to make the numbers easier to multiply.